Exploitation touristique des ressources naturelles et développement durable. Cas du site touristique des Cascades de Karfiguéla au Burkina Faso - Babou Eugène Ido (Études Caribéennes)
The sustainable management of natural resources used in tourism is a major challenge for managers of tourist sites. The survival of the tourism sector in areas with high natural potential depends on actions to enhance and preserve these resources.This research aims to understand the challenges of the tourism exploitation of natural resources on sustainable development. As the term sustainable development is broad, the study was circumscribed by taking into account two dimensions: the economy and the environment. The reflection was carried out on the Karfiguéla waterfall, put into tourism since 1999, through the following central research question: does the tourism of natural resources contribute to both economic development and preservation of the environment? From this central question, two specific questions emerged: What is the contribution of the tourism of the waterfalls to the endogenous economic development of the village of Karfiguéla? What is the contribution of the tourist use of the waterfalls to the preservation of the site’s environment?To answer these questions, after a literature review, we mobilized two theoretical approaches, development anthropology and conservationism, as entry points to explore the subject. In addition, we have adopted a methodological approach at the crossroads of sociology, anthropology and geography and a mixed approach (quantitative and qualitative) for data collection.The tourist exploitation of the waterfall resource has brought added value in the village of Karfiguéla, but this is low in view of the reputation of the site and this in comparison with other sites at the national level. In addition, the preservation of the environment has not followed this tourist exploitation. The situation of environmental degradation is alarming since there are actions of degradation and pollution, on the one hand, by tourists and also by residents.The correlation between the economy and the environmental pillar of sustainable development shows that there is an imbalance.